Happiness training effect on primary school teachers’ academic burnout and teaching effectiveness: narratives from teachers - Liu, Yongmei; Xie, Jian (BMC Psychology, 2025)
Background Teacher burnout has become a critical issue in education, significantly affecting teaching effectiveness and student outcomes. Positive psychological interventions, such as happiness training, have the potential to mitigate burnout and enhance teachers’ well-being. However, empirical evidence on the effectiveness of such interventions in educational settings remains limited. Objectives This study aimed to investigate the impact of happiness training on reducing academic burnout and improving teaching effectiveness among primary school teachers. It also explored teachers’ narratives to better understand their experiences following the intervention. Method An explanatory sequential mixed-method research design was employed. The quantitative phase involved 200 primary school teachers who attended a happiness training workshop. A pretest-posttest-follow-up design was used, and data was analyzed using repeated measures ANOVA. The qualitative phase involved narratives from five teachers, which were interpreted to extract themes related to their experiences post-training. Results Quantitative results showed significant reductions in burnout and improvements in teaching effectiveness post-intervention ( p < 0.05). In the qualitative phase, thematic analysis of teacher narratives revealed eight. The main themes identified in the narratives of teachers participating in the happiness training include emotional exhaustion and recovery, reconnection with purpose, improved classroom engagement, stress management techniques, positive relationships with students and colleagues, increased job satisfaction, work-life balance, and sustained professional growth. Conclusions Happiness training significantly reduced burnout and improved teaching effectiveness among primary school teachers. The qualitative insights further highlighted personal and professional growth following the intervention. These results underscore the importance of integrating well-being programs into teacher development initiatives to foster sustainable educational outcomes.